Telemedicine dan Telenursing untuk Manajemen Pasien Rawat Jalan Selama Pandemi COVID-19: A Literatur Review - Suara, Eviwindha; Retnaningsih, Dwi (Jurnal Manajemen Asuhan Keperawatan; Vol 6 No 2 (2022): Jurnal Manajemen Asuhan KeperawatanDO - 10.33655/mak.v6i2.130, 2022)
Background: The coronavirus disease-19 (COVID-19) outbreak is a public health emergency of international concern. Telemedicine and telenursing are effective options to combat the COVID-19 outbreak by minimizing contact between patients and reducing staff exposure. This literature review aims to identify the role of telemedicine and telenursing services in preventing, diagnosing, treating, and controlling disease during the COVID-19 outbreak. Methods: This article is a literature review. The data search was carried out by conducting a comprehensive literature review based on major international and national databases (Pubmed, google scholar). The data search was carried out by reviewing journals from 2012 to 2021. The literature review reviewed by researchers did not focus on randomized controlled trials (RCTs) and controlled studies only, but all research related to the covid 19 pandemic and telemedicine and telenursing. Results: 11 studies met inclusion from 66 search results. Telemedicine and telenursing are certainly appropriate in minimizing the risk of transmitting COVID-19. This solution has the potential to prevent all forms of direct physical contact, provide continuous care to the community, and ultimately reduce morbidity and mortality in the COVID-19 outbreak. Conclusion: The use of telemeicine and telenursing improves the provision of health services. Therefore, telemedicine and telenursing must become important tools in care services while keeping patients and health care providers safe during the COVID-19 outbreak.